2011
DOI: 10.1021/ie101963k
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of the Fenton Process by Increasing the Temperature

Abstract: The effect of temperature on the Fenton process has been studied within the range of 25−130 °C using phenol (100 mg/L) as target compound, 10 mg/L Fe2+, and a dose of H2O2 corresponding to the theoretical stoichiometric amount (500 mg/L) for mineralization. The TOC reduction was considerably improved as temperature increased. Whereas at 25 °C the TOC decreased less than 28%, a reduction of almost 80% was achieved at 90 °C. Beyond this temperature no significant improvement of mineralization was observed, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 174 publications
(99 citation statements)
references
References 34 publications
10
80
0
Order By: Relevance
“…It has to be highlighted the potential of magnetite as CWPO catalyst under the testing conditions due to its high activity and remarkable stability. Moreover, the mineralization percentage achieved was even higher than the obtained upon homogeneous Fenton oxidation under similar working conditions [27].…”
Section: Magnetic Natural Mineralsmentioning
confidence: 69%
See 2 more Smart Citations
“…It has to be highlighted the potential of magnetite as CWPO catalyst under the testing conditions due to its high activity and remarkable stability. Moreover, the mineralization percentage achieved was even higher than the obtained upon homogeneous Fenton oxidation under similar working conditions [27].…”
Section: Magnetic Natural Mineralsmentioning
confidence: 69%
“…A slight decrease of catalytic activity was observed upon three consecutive runs, which was attributed to small leaching of iron from the solid. Despite the fact that several magnetic minerals have shown to be fairly stable in the process, the degradation rates observed are still far from those of homogeneous Fenton oxidation under similar operating conditions [27]. With the aim of improving the activity of the catalysts and thus, increasing the oxidation rate, the effect of including other metals into the magnetite structure by isomorphic substitution of Fe has been studied by several authors [37-39, 57, 58] were directly related to the amount of iron leached, which decreased upon the three successive runs (13, 6 and 4 mg L -1 measured in the liquid phase).…”
Section: Magnetic Natural Mineralsmentioning
confidence: 94%
See 1 more Smart Citation
“…All the acids were mineralized except oxalic which showed to be refractory to Fenton oxidation even at those higher temperatures. Zazo et al [40] reported that oxalic acid can be mineralized upon Fenton oxidation at around 100°C. Fig.…”
Section: Oxidation Byproductsmentioning
confidence: 99%
“…Currently, many technologies have been developed to improve Fenton oxidation for removing organic contaminants from aqueous solutions, such as photo-assisted (Al Momani et al, 2006;Kusic et al, 2006;Lau et al, 2002), microwave-enhanced (Liu et al, 2013;Yang et al, 2009), heating (Pliego et al, 2012;Zazo et al, 2011), and quinone (Chen and Pignatello, 1997;Gomez-Toribio et al, 2009) and hydroxylamine hydrochloride (HA) (Chen et al, 2011) redox cycling. As mentioned above, a major drawback of the Fenton system has been the accumulation and hydrolysisprecipitation of ferric ions, which could further slow down the whole Fenton process.…”
Section: Introductionmentioning
confidence: 99%